Development Of The Malaysian Skills Certification For Lecturers In Tertiary TVET Institutions - Che Amran, Aliza; Mat Hanafiah, Mohd Ariff; Ananta, Gede Pramudya; Ali, Adlan; Che Ku Mohd, Che Ku Nuraini (Penerbit UTHM, 2020)
Competency framework is a tool that sets out and defines a list of competencies that is required for a profession. It is a framework that a profession needs to perform their job effectively. This paper discusses a competency framework developed for technical lecturers under the Malaysian Skills Certification (Sijil Kemahiran Malaysia - SKM). TVET lecturers are tertiary level educators who teach practice and application oriented (PAO) based programmes at technical universities. The competency framework was developed using DESCUM (Develop a Standard Curriculum) method. The framework was published as an occupational standard under the National Occupational Skill Standard (NOSS) for TVET Implementation and Development. Nine competency units identified to be critical and important for a TVET lecturer to have are described in this paper. It comprises eight core competency units and one elective competency unit with thirty-four work activities. The work activities cover the roles and responsibilities of a lecturer, namely teaching, research and publication as well as consultation services. It is hoped that the competency framework for TVET lecturers will be a platform to assure the quality of TVET education at tertiary level and improve the Malaysian national higher education and economic landscape in the long run.